2020
DOI: 10.1111/jth.15036
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety and efficacy of N8‐GP in previously treated pediatric patients with hemophilia A: Final results from pathfinder5

Abstract: Background N8‐GP (turoctocog alfa pegol; Esperoct®, Novo Nordisk A/S, Bagsvaerd, Denmark) is a glycoPEGylated, extended half‐life human recombinant factor VIII (FVIII). Objective Here, we report end‐of‐trial safety and efficacy results from the completed N8‐GP pathfinder5 trial. Methods pathfinder5 (NCT01731600) was a multi‐national, open‐label, single‐arm, non‐randomized, non‐controlled trial in previously treated male patients aged <12 years old with severe hemophilia A that comprised a main and an extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 12 publications
3
32
0
Order By: Relevance
“…The hemostatic effect of N8‐GP for treatment of bleeding episodes was confirmed in both the pathfinder2 and pathfinder5 trials 9,10 . In adolescents and adults, 83.2% of all bleeds were successfully treated with N8‐GP, and 94.9% were treated with ≤2 doses.…”
Section: Overview Of Key Results From the Pathfinder Programmentioning
confidence: 80%
See 4 more Smart Citations
“…The hemostatic effect of N8‐GP for treatment of bleeding episodes was confirmed in both the pathfinder2 and pathfinder5 trials 9,10 . In adolescents and adults, 83.2% of all bleeds were successfully treated with N8‐GP, and 94.9% were treated with ≤2 doses.…”
Section: Overview Of Key Results From the Pathfinder Programmentioning
confidence: 80%
“…Both pathfinder2 (adolescents and adults) and pathfinder5 (children) trials concluded in 2018, and final EOT results covering the entire study periods (main and extension phases) are presented in the accompanying articles within this Supplement 9,10 . In pathfinder2, 186 patients in total (25 adolescents and 161 adults) were exposed to N8‐GP for a total of 66 577 exposure days (EDs), with a total trial time of 785 years.…”
Section: Overview Of Key Results From the Pathfinder Programmentioning
confidence: 99%
See 3 more Smart Citations